Utilization of Effective Leakage flux using Wireless Power Transmission in Induction Stove - Kumaresan, J.; Saravanan, C.; Thiruvenkadam, A.S.; Surya, P. (International Journal of Psychosocial Rehabilitation, 2019)
This paper implements the concept of Wireless Power Transfer (WPT) between the two coils related to the induction stove. At the time of cooking, the oscillating magnetic flux in the induction stove used to cook the food. Here a thin circularly wounded flat coil kept in between the induction stove and the cookware. So, EMF gets induced in a coil based on Faraday’s law of an Electro-Magnetic Induction (EMI). This Electro-Motive Force (EMF) used to charge a battery that can be used as an emergency power source or directly connected to the load. Also, the leakage flux of the induction stove is utilized by a load with the help of a flattened copper coil. This prototype also explains the WPT and gives an idea in real-time applications